NITROGEN IN FUTURE BIOSPHERE STUDIES - Boyd S.R. (My University, 2001)
This article suggests a theme for future nitrogen studies, involving the functioning and evolution of the biosphere, together with certain aspects of human biology. It is hoped that this theme could be developed into a multi-authored book at some point in the future, although numerous new case studies may be required.The biosphere can be considered to be a single interactive system, comprised of numerous component parts, including the atmosphere, rain, rivers, lakes, oceans, continental ecosystems, marine ecosystems, soils and sediments. In order to study the internal complexity of each of the components, and the relationships that exist between them, one can choose a common theme. The author believes that nitrogen is a good prospect because of its ubiquitous nature and complex chemistry.The burial of sedimentary volatiles in the continental crust has contributed to the long-term chemical evolution of the exterior environments of the Earth. The most marked effects, notably the accumulation of atmospheric oxygen, have been due to the burial of reduced carbon. An understanding of the passage of sedimentary volatiles through the crust will provide important constraints on the evolution of the biosphere, and may lead to a more meaningful comparative planetology. Carbon is difficult to trace through crustal processes because its high temperature form (graphite) is incompatible with the crystal structures of silicate minerals. However, the high temperature form of sedimentary nitrogen (ammonium) readily enters into potassic minerals, and it can be easily traced through crustal processes.Herein, the fate of sedimentary nitrogen is traced from wet sediments, through metamorphic rocks, into granites and other crustal melts. Without the trapping of nitrogen in the crust, and the liberation of oxygen that is a consequence of biological nitrogen fixation, the N2/O2 of the atmosphere may have been about 82.9% to 16.3%, and the total atmospheric pressure about 1.2 atm. Most of the changes in the oxygen content is due to dilution by nitrogen, with only about 5% of the present atmospheric oxygen being a consequence of nitrogen fixation.The ancient continental surfaces would have been volcanic deserts containing little (<1 ppm) or no nitrogen. today, nitrogen-rich soils support continental ecosystems. one can use nitrogen as a 'window' to speculate on the colonisation of continents by land plants. herein, fixation legumes is considered in detail, and drawing analogies with present day, author speculates plants.having speculated co-evolution atmosphere, ecosystems, place human being centre tropical forest, begin examine how they relate modern biosphere. chosen example metabolism plant protein, roles glutamate dehydrogenase (gdh), vitamin b2, and flavin mononucleotide (FMN).The realisation of this theme would imply numerous new case studies, notably those concerning the continental crust, where nitrogen studies were linked to mineralogy, petrology and other geochemical tracers, including Sr, O, Al, and K, and where the short-range order of δ15N were taken into consideration.
Keywords: BIOSPHERE; BIOGEOCHEMISTRY; CONTINENTAL CRUST; NITROGEN CYCLE; NITROGEN FIXATION; LAND PLANTS; HUMAN METABOLISM